HUBUNGAN MENGUNYAH PERMEN KARET DENGAN FUNGSI EKSEKUTIF PADA MAHASISWA KEDOKTERAN - Michael Salim, Yuda Turana, Dewi (NEURONA, 2013)
INTRODUCTION LATEST RESEARCH SHOWED THAT CHEWING GUM CAN IMPROVE COGNITIVE FUNCTION MAINLY ATTENTION AND WORKING MEMORY BUT STILL THERE IS NO CLEAR RELATIONSHIP BETWEEN CHEWING GUM AND EXECUTIVE FUNCTION